Demographic and microbial characteristics and drug resistance of childhood tuberculosis in Istanbul: analysis of 1,541 cases - ERDEM ERALP, ELA (J INFECTION DEVELOPING COUNTRIES, 2014)
Introduction: Although tuberculosis (TB) is frequently seen in Turkey, there are limited studies on childhood TB. We aimed to describe clinical and laboratory findings, including drug resistance, of children with TB in Istanbul, Turkey. Methodology: The study included all children aged 0-14 years who were registered in public dispensaries between 2006 and 2010. Results: The study included 1,541 cases. Forty-four percent (n = 763) of the patients were male with a mean age of 8.86 +/- 4.19 years. Fifty-five percent of the patients had pulmonary TB, 39% had extrapulmonary TB, and 6% had both pulmonary and extrapulmonary TB. The most common extrapulmonary involvement sites were the pleura (n = 193), lymph nodes (n = 247), and central nervous system (n = 41). Forty-one percent of the patients were evaluated microbiologically and 35% of them were positive. For the total study group, 14% of them were positive. A drug susceptibility test was performed on 108 patients. Drug resistance to at least one drug was detected in 16% (n = 17), to isoniazid in 15% (n = 16), streptomycin in 12% (n = 12), rifampicin in 9% (n = 10), ethambutol in 7% (n = 8), and multi-drug resistance in 8% (n=9) of patients. Conclusions: This is the largest analysis on demographic features and drug resistance of childhood TB in Turkey. In Turkey, the rate of microbiological diagnosis is low, similar to rates worldwide. More microbiological studies and drug resistance tests should be done and annual changes should be followed with multi-center studies.
Keywords: tuberculosis; child; pediatric; drug resistance; Turkey; GLOBAL EPIDEMIOLOGY; CHILDREN